A Case Study On HSBC's Corporate Strategies In Economy Crisis (IRAT) - Xiaoling, Chen (2009)
In this study, it explains HSBC's overall portfolio, company background, vision and mission, organizational structure, research and development. Also, HSBC's overall performance in current world wide economy crisis has been analyzed.